Life cycle assessment on the environmental impacts of different pig manure management techniques - Dong, Baocheng; Song, Chengjun; Li, Huibin; Lin, Aijun; Wang, Jiuchen; Li, Wei (International Journal of Agricultural and Biological Engineering, 2022)
The management of livestock waste is an effective way to achieve emission reduction and carbon fixation in agriculture and rural areas. At present, aerobic composting and anaerobic fermentation are widely used in livestock waste treatment technology. In this study, pig manure management was taken as an example, a comprehensive environmental load index was constructed to quantitatively evaluate the environmental impacts of global warming, environmental acidification, eutrophication, and photochemical ozone synthesis during aerobic composting and anaerobic fermentation based on the life cycle assessment. The results showed that the potential values of aerobic composting and anaerobic fermentation were similar, and the order was global warming, environmental acidification, eutrophication, and photochemical ozone synthesis. Anaerobic fermentation contributed more to global warming, while aerobic composting contributed more to environmental acidification, eutrophication, and photochemical ozone synthesis. In addition, the environmental load index of aerobic composting was significantly higher than that of anaerobic fermentation. There were certainly regional differences in the environmental load index, and the environmental impact effect of anaerobic fermentation was low and more environmentally friendly. These findings provided a technical basis for livestock manure management in different regions of China, which was conducive to promoting animal husbandry emission reduction and carbon sequestration. Keywords: manure management, life cycle assessment, low carbon treatment, aerobic composting, anaerobic fermentation, environmental impact assessment, emission reduction and carbon sequestration DOI: 10.25165/j.ijabe.20221503.6212 Citation: Dong B C, Song C J, Li H B, Lin A J, Wang J C, Li W. Life cycle assessment on the environmental impacts of different pig manure management techniques. Int J Agric & Biol Eng, 2022; 15(3): 78–84.